Chapter Il suffisso verbale -yva-/-iva- in testi slavo-orientali dei secoli XI-XIV - Ruvoletto, Luisa (Biblioteca di Studi Slavistici, 2016)
The article focuses on the main uses of secondary imperfective verbs with the suffix -yva-/-iva- in Early East Slavic texts dated 11th-14th centuries. The verbs with this suffix are used in all different contexts where the imperfective verbal aspect is required. The examples from the texts show a more frequent occurrence of the verbal forms with the suffix in dialogues, that is in passages involving oral communication contexts. Only in the later centuries the suffix will also take the particular function of expressing the "iterative mode of action" (iterativnyj sposob dejstvija).